Enzyme-responsive polyion complex (PIC) nanoparticles for the targeted delivery of antimicrobial polymers. Issue 15 (24th March 2016) - Insua, Ignacio; Liamas, Evangelos; Zhang, Zhenyu; Peacock, Anna F. A.; Krachler, Anne Marie; Fernandez-Trillo, Francisco
Abstract : Here we present new enzyme-responsive polyion complex (PIC) nanoparticles prepared from antimicrobial poly(ethylene imine) and an anionic enzyme-responsive peptide targeting Pseudomonas aeruginosa 's elastase. Abstract : Here we present new enzyme-responsive polyion complex (PIC) nanoparticles prepared from antimicrobial poly(ethylene imine) and an anionic enzyme-responsive peptide targeting Pseudomonas aeruginosa 's elastase. The synthetic conditions used to prepare these nanomaterials allowed us to optimise particle size and charge, and their stability under physiological conditions. We demonstrate that these enzyme responsive PIC nanoparticles are selectively degraded in the presence of P. aeruginosa elastase without being affected by other endogenous elastases. This enzyme-responsive PIC particle can exert an elastase-specific antimicrobial effect against P. aeruginosa without affecting non-pathogenic strains of these bacteria. These targeted enzyme-responsive PIC nanoparticles constitute a novel platform for the delivery of antimicrobial peptides and polymers, and can be a powerful tool in the current race against antimicrobial resistance.